2008
DOI: 10.1016/s1726-4901(08)70159-x
|View full text |Cite
|
Sign up to set email alerts
|

Behcet's Disease with Uveitis in Taiwan

Abstract: Visual outcome is poorer in males than in females and has improved in the recent decade, but still a significant proportion of patients lose their vision quickly. The number of new patients has not decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
12
0
1
Order By: Relevance
“…In studies from different parts of the world, panuveitis was reported as the most frequent ocular manifestation in patients with Behçet uveitis. 17,20,23,24 In our patients, the commonest manifestation was retinal vasculitis associated with anterior uveitis and then panuveitis. One-fifth of our patients manifested hypopyon formation at some point in their follow-up.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In studies from different parts of the world, panuveitis was reported as the most frequent ocular manifestation in patients with Behçet uveitis. 17,20,23,24 In our patients, the commonest manifestation was retinal vasculitis associated with anterior uveitis and then panuveitis. One-fifth of our patients manifested hypopyon formation at some point in their follow-up.…”
Section: Discussionmentioning
confidence: 55%
“…Studies in the literature reported similar rates of expression of HLA-B51 antigen in Behçet uveitis with consistency across populations from NSR and SR countries. [14][15][16][17][18] Overall, the two patient populations showed similar demographic features. In both subgroups, the majority of patients was male and had bilateral disease.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…1). The disease can be highly threatening to vision because final visual acuity can be worse than 20/200 in 19-28% of patients [60,61]. The main causes of visual impairment in these patients were macular scar, optic nerve atrophy, and phthisis bulbi after multiple recurrences.…”
Section: Behcet's Diseasementioning
confidence: 99%
“…Il existe cependant une préférence pour certains tissus et organes. Parmi les différentes atteintes de la MB, l'atteinte cutanéo-muqueuse est celle qui s'associe le plus souvent à l'atteinte oculaire (14,15,16). Dans notre étude le taux de cécité était de 18,2 %.…”
Section: Caractéristiques Des Patients Atteints D'une Maladie De Behçunclassified